THE CHARACTERS’ ATTACHMENT STYLE IN OUR BELOVED SUMMER (2021) - Gusthafo, Colli Brey (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
Our Beloved Summer (2021) which depicts two main characters with different life backgrounds, mindsets, and attachment styles living a relationship. Choi Ung who grew up full of parental affection, while Kook Yeon Su who had no parental affection at all. This gives rise to several attitudes that describe how each character's attachment style is when living in a relationship. This study seeks to show how the attachment style of each character in this drama is by using the theory of Hazan and Shaver (1987) regarding adult attachment. This study states that there are 3 attachment styles, namely secure, anxious, and avoidant. This research concludes that the character of Choi Ung here is a safe figure while Kook Yeon Su is an anxious and avoidant figure. Keywords: Attachment Style, Anxious, Avoidant, Secure, Relationship